Thelypteris sylva-nipponica, a new allotetraploid species in the Parathelypteris group (Thelypteridaceae) - Ebihara, Atsushi; Nakato, Narumi; Ohi-Toma, Tetsuo; Iwatsuki, Kunio (Phytotaxa, 2020)
A broad-leaved form of Thelypteris nipponica, usually called “var. borealis”, was identified as an allotetraploid originated from hybridization between two diploid species T. nipponica and T. musashiensis based on chromosome number, plastid rbcL sequence and nuclear gapCp “short” sequence. We found that the original material of Thelypteris nipponica var. borealis morphologically corresponds not to the plant widely known as “var. borealis” but to diploid T. nipponica. Therefore, we described the tetraploid distributed in Japan and China as a new species, Thelypteris sylva-nipponica.